Endometriosis pathoetiology: The role of micrornas in the dysregulation of endometrial functions - Jiahui Zhang; Isabelle Baptista; Ping Xia; Bhuchitra Singh (Reproductive and Developmental Medicine, 2019)
Endometriosis is a common gynecological disorder characterized by pelvic pain, heavy menstruation, and infertility. The clinical diagnosis of endometriosis is often delayed 8–10 years after the onset of symptoms due to the lack of an effective and reliable noninvasive diagnostic method. In recent years, a number of research studies have reported using microRNAs (miRNAs) as potential noninvasive biomarkers for diagnosing endometriosis. Because miRNAs regulate gene expression, the differential expression of miRNAs in endometriosis patients also provides insight on dysregulated gene expressions in the pathogenesis of endometriosis. In this review, a number of global profiling studies (published through July 2019) that investigated the differential expression of miRNAs in endometriosis were identified. Based on these findings, the role of miRNAs in the pathogenesis of endometriosis, particularly with regard to the dysregulation of endometrial functions, cell cycle regulation, proliferation of endometrial stromal cells, and angiogenesis, was discussed. The potential of these miRNAs as noninvasive diagnostic biomarkers of endometriosis was also discussed.